DETECTION OF FACTORS THAT AFFECT THE DECLINE IN COGNITIVE FUNCTION THAT CAUSES DEMENTIA IN THE ELDERLY - Astutik, Nanik Dwi; Kuntoro, Kuntoro; Indawati, Rachmah; Fernanndes, Angelina da Costa (Jurnal Biometrika dan Kependudukan, 2024)
In general, the number of elderly people suffering from dementia is expected to increase. Dementia results in a decrease in the quality of life of sufferers so that it becomes a problem. This study aims to detect and identify factors that affect the decline in cognitive function that causes dementia in the elderly. This type of analytical research is conducted by the cross sectional research method. The population of this study is the elderly in Malang city, east Java, the sample size is 155 people with probability sampling technique using proportionate cluster random sampling. Data Collection for the identification of cognitive aspects using instruments MMSE (Mini Mental Status Exam) instruments, data analysis using the Bier Logistic Regression test with SPSS20 for Windows. The results of the analysis showed the relationship between health status factors and the cognitive function of the elderly (p value 0.05). The results that some respondents as many as 105 people or 67,7% had normal cognitive function, and 50 respondents or 32.3% fell into the category of probable cognitive impairment. Conclusion  were  obtained  that  the  decline  in cognitive function in the elderly was caused by  high  blood  pressure,  smoking,  having  experienced  a  blow to  the head, a sad mood, lack of exercise, lack of activity in social activities, difficulty sleeping, and prolonged illness and illness. The suggestion from the results  of  this study is that the elderly manage and prevent risk factors so that cognitive function does not decline so that dementia can be prevented.